ANALISIS INVERSI WAVEFORM TIGA KOMPONEN UNTUK MENENTUKAN MOMEN TENSOR GEMPA BUMI DI PULAU JAWA - Muh. Rodli Masykur, ; Bagus Jaya Santosa, (Matematika dan Sains, 2011)
IRIS noted 294 earthquakes happened in Indonesia, 28 of them in Java island. Seismogram analysis used three component waveform to obtain tensor moment and to know the broken plane pattern of subduction in Java. Research was started with requesting of quake data from IA and or geofon. Using ISOLA software it had been conducted convertion and data preprocessing, input of data consisted of: crustal model, event info, choising station, preparing raw data and defining seismic source, counting Green function, invertion, and plot of invertion product. Futher drawing fault-plane caused earthquake used hcplot software. Analysis results showed that tensor moment at 11 Agustus 2010 as much as Mrr = -1.629, Mtttt = 0.983, Mpppp = 0.645, Mrtrt = 1.820, Mrprp = -1.449, Mtptp = -0.761 and at 9 Nopember 2010 as much as Mrrrr = 0.613, Mtttt = -0.172, Mpppp = -0.441, Mrtrt = 0.232, Mrprp = -0.203, Mtptp = -0.309. The broken plane pattern growing at each were normal fault and reverse fault line with island. IRIS noted 294 earthquakes happened in Indonesia, 28 of them in Java island. Seismogram analysis used three component waveform to obtain tensor moment and to know the broken plane pattern of subduction in Java. Research was started with requesting of quake data from IA and or geofon. Using ISOLA software it had been conducted convertion and data preprocessing, input of data consisted of: crustal model, event info, choising station, preparing raw data and defining seismic source, counting Green function, invertion, and plot of invertion product. Futher drawing fault-plane caused earthquake used hcplot software. Analysis results showed that tensor moment at 11 Agustus 2010 as much as Mrr = -1.629, Mtttt = 0.983, Mpppp = 0.645, Mrtrt = 1.820, Mrprp = -1.449, Mtptp = -0.761 and at 9 Nopember 2010 as much as Mrrrr = 0.613, Mtttt = -0.172, Mpppp = -0.441, Mrtrt = 0.232, Mrprp = -0.203, Mtptp = -0.309. The broken plane pattern growing at each were normal fault and reverse fault line with island.